PENGARUH RETURN SAHAM, KOMPENSASI MANAJEMEN, DAN NILAI PERUSAHAAN TERHADAP INCOME SMOOTHING (Studi Empiris pada Perusahaan Sektor Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2021-2024) - Lika T Siringoringo; Siti Mutmainah (Diponegoro Journal of Accounting, 2026)
This study aims to analyze the effect of stock returns, management compensation, and firm value on income smoothing practices among manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2024 period. Data were collected using the purposive sampling method and subsequently analyzed using linear regression for cross-sectional data. The study sample consisted of 60 companies, resulting in a total of 240 observations over a four-year period. Data processing was conducted using SPSS version 26. The results indicate that stock returns, proxied by the Dividend Payout Ratio (DPR), and management compensation, proxied by the bonus plan, do not have a positive effect on income smoothing. In contrast, firm value, proxied by the Price Earnings Ratio (PER), has a positive influence on a company's decision to engage in income smoothing practices.